Levels of knowledge about the glycemic index concept among women with gestational diabetes mellitus - Mohd Anuar, Norfarhana; Mohd Yusof, Barakatun Nisak; Hasbullah, Farah Yasmin; Adznam, Siti Nur’Asyura; Ibrahim, Zuriati; Zakaria, Nor Fadhlina; Hashim, Norkamaliah (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2020)
Introduction: Low glycemic index (GI) diet is recommended as part of medical nutrition therapy for the management of gestational diabetes mellitus (GDM). While the clinical benefits are evident, data assessing knowledge of the GI concept among women with GDM are scarce. This was a needs assessment study to determine the level of knowledge about the GI concept among women with GDM. Methods: Using a cross-sectional design, we included 85 women with GDM (mean age: 30.6 ± 4.0, pre-pregnancy BMI: 24.8 ± 4.1 kg/m2, gestational age: 34.0 ± 4.0 weeks) from Hospital Serdang, Malaysia. Knowledge about the GI concept was assessed using a developed questionnaire. Additional questions on GDM were assessed using Gestational Diabetes Mellitus Knowledge Questionnaire (GDMKQ). Subjects with less than 50%, 51-74%, and more than 75% total score were categorized as having poor, fair, and good knowledge levels, respectively. Results: The mean knowledge score obtained by the subjects was 12.8 ± 3.5. More subjects scored correctly for GDM-related knowledge (68.2%). More than half (58.8%) had heard about the GI concept previously and 55.3% understood the definition of GI. The average knowledge score about the GI concept was 55.6%; subjects scored highest on the influence of different carbohydrates (teh tarik versus milk) on blood glucose level (87.1%). However, the majority of the subjects had fair knowledge level (62.4%). Conclusion: Women with GDM had moderate knowledge about the GI concept. Results of the needs assessment served as preliminary data for the development of a GI-based nutrition education program in Malaysia.